Heterogeneous kimberlite metasomatism revealed from a combined He-Os isotope study of Siberian megacrystalline dunite xenoliths. (1st December 2019) - Pernet-Fisher, John F.; Barry, Peter H.; Day, James M.D.; Pearson, D. Graham; Woodland, Sarah; Agashev, Aleksey M.; Pokhilenko, Lyudmila N.; Pokhilenko, Nikolay P.
Abstract: The Siberian sub-continental lithospheric mantle (SCLM) is regionally heterogeneous due to the complex modification of ancient cratonic material by various metasomatic fluids and interaction with the Siberian plume at ∼250 Ma. Here, we assess the extent and origin of this heterogeneity by analysis of helium isotopes, rhenium-osmium isotopes, trace-element, and highly siderophile element [HSE: Os, Ir, Ru, Pt, Pd, Re] abundances in a suite of mantle-derived megacrystalline dunite xenoliths from the 360 Ma Udachnaya East kimberlite pipe, Siberia. This enables assessment of the style and extent of metasomatism acting to modify the volatile budget of the Siberian SCLM. The olivine megacrysts have 3 He/ 4 He values that range from 2.3 to 7.4 RA (where RA = the 3 He/ 4 He of air), outside the canonical range for the lithospheric mantle (6.1 ± 2.1 RA ; Day et al., 2015). High [He] and low U + Th concentrations in these olivine megacrysts indicate that the Udachnaya megacrystalline dunite xenolith suite has undergone minimal post-eruptive modification of He isotopes by 4 He recoil. We instead interpret He isotope variations to reflect pre- or syn-eruptive metasomatic signatures during kimberlite emplacement. The dunites can be divided into two groups, ultimately reflecting modification by two distinct metasomatic styles. Group 1 dunites are characterized by highly unradiogenic Os isotope compositions (γOs360Ma −16 to −13) and ancient melt depletion ages (∼3 Ga) typical of ancient cratonic lithospheric mantle; yet display a range of He isotope ratios (2.3–5.9 RA ). This indicates that group 1 dunites have been modified by gas-rich metasomatic fluids acting to change He abundances and isotope ratios, while preserving unradiogenic Os isotope and HSE abundance systematics. Group 2 dunites extend to significantly more radiogenic Os isotope signatures and higher He isotope values (γOs360Ma > −5 to +53; 3 He/ 4 He from 3.7 to 7.4 RA ). These two groups define a negative hyperbolic array between Os and He isotopes which we interpret to result from metasomatism by variable mixtures between: (1) a gas-rich and HSE-poor fluid (similar to the fluids acting to modify Group 1 dunites) with helium isotope compositions above the MORB range (>8 RA ) derived from the asthenosphere, and: (2) strongly radiogenic fluids (∼2 RA ; 187 Os/ 188 Os > 0.25) likely sourced from within the SCLM. The Udachnaya megacrystalline dunite xenolith suite provides insight into how mantle-plume derived fluids interact with metasomatic fluids within the SCLM.